Challenges for monetary and fiscal policy interactions in the postpandemic era - Dennis Bonam; Matteo Ciccarelli; Sandra Gomes (European Central Bank (ECB), 2024)
In the low inflation and low interest rate environment that prevailed over the period 2013-2020, many argued that besides expansionary monetary policy, expansionary fiscal policy could also support central banks' efforts to bring inflation closer to target. During the pandemic, proper alignment of fiscal and monetary policy was again crucial in promoting a rapid macroeconomic recovery. Since the end of 2021 an environment of higher inflation, lower growth, higher uncertainty, and higher interest rates has changed the nature of the required policy mix and poses different challenges to the interaction between monetary and fiscal policy. Following up on the work done under the ECB's 2020 strategy review (see Debrun et al., 2021), this report explores some of the renewed challenges to monetary and fiscal policy interactions in an environment of high inflation. The main general conclusion is that, with an independent monetary policy that aims to bring inflation back to target in a timely manner, it is still possible to design fiscal policy in a way that protects vulnerable parts of society against the costs of high inflation without pulling against the central bank's effort to tame inflation. This is more likely to be the case if fiscal measures are temporary and targeted, and if priority is given to structural reforms and public investment in support of potential growth. The latter is particularly effective in reshaping the supply side of the economy in a manner that is likely to have a lasting positive structural impact.
Keywords: E22; E52; E58; E62; 330; monetary policy; fiscal policy; public investment